2012
DOI: 10.1371/journal.pone.0044307
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic Phosphorylation of Histone H3 on Ser-10 by Protein Kinase Cδ

Abstract: Phosphorylation of histone H3 on Ser-10 is regarded as an epigenetic mitotic marker and is tightly correlated with chromosome condensation during both mitosis and meiosis. However, it was also reported that histone H3 Ser-10 phosphorylation occurs when cells are exposed to various death stimuli, suggesting a potential role in the regulation of apoptosis. Here we report that histone H3 Ser-10 phosphorylation is mediated by the pro-apoptotic kinase protein kinase C (PKC) δ during apoptosis. We observed that PKCδ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 34 publications
(38 reference statements)
1
35
0
Order By: Relevance
“…When activated, PKCδ translocates to the nucleus [33] and, possibly through JNK signals, promotes proximal regulation of apoptosis through cytochrome C release, PARP cleavage, histone phosphorylation [34], and caspase 3 activation. Nuclear retention can be prolonged and intensified by generation of the catalytic fragment of PKCδ by caspase 3 [33].…”
Section: Pkcδ Structure Activation Regulation and Role In Apoptosismentioning
confidence: 99%
“…When activated, PKCδ translocates to the nucleus [33] and, possibly through JNK signals, promotes proximal regulation of apoptosis through cytochrome C release, PARP cleavage, histone phosphorylation [34], and caspase 3 activation. Nuclear retention can be prolonged and intensified by generation of the catalytic fragment of PKCδ by caspase 3 [33].…”
Section: Pkcδ Structure Activation Regulation and Role In Apoptosismentioning
confidence: 99%
“…Immunoblotting analysis was performed as we previously described [30,31]. For immunoprecipitation, cell lysates were prepared in lysis buffer (20 mM Tris-HCl, pH 7.5, 150 mM NaCl, 1 mM EDTA, 1 mM EGTA, 1% Triton X-100, 2.5 mM sodium pyrophosphate, 1 mM β-glycerol phosphate, 10 μg/ml pepstatin A, 10 μg/ml leupeptin, 1 mM PMSF, 10 μg/ml aprotinin, 10 mM NaF, and 1 mM Na 3 VO 4 ).…”
Section: Immunoblotting and Immunoprecipitationmentioning
confidence: 99%
“…AH3Lys9 has been found to decline during the first four days of neural differentiation of human embryonic stem cells (hESC) then levels gradually increase during days 4–8 as it is believed to play a dual role in hESC pluripotency maintenance and neural differentiation and is generally associated with an open chromatin state and increased transcriptional competency (Lee and Mahadevan 2009; Peterson and Laniel 2004; Qiao et al 2015). Similar to proliferating hPNCs exposed to CP, differentiating cells exposed to As had an increase, relative to controls, of pAH3Ser10 that suggests a shift to active gene transcription and apoptosis (Koch et al 2007; Lo et al 2000; Park and Kim 2012). Activation of the apoptosis pathway was confirmed with high proportions of apoptotic cells with cell status imaging but not with concomitant increases in caspase 3.…”
Section: Discussionmentioning
confidence: 89%
“…In our hNPC culture system, each toxicant altered the presence of at least one histone modification measured in a differentiation stage-specific manner. Specifically, we found that proliferating hNPCs treated with CP had increased expression of phosphorylated serine 10 in histone H3 (pAH3Ser10) which is functionally linked to apoptosis through PKCδ phosphorylation and Aurora B and VRK1-mediated chromatin condensation during mitosis (Crosio et al 2002; Kang et al 2007; Park and Kim 2012). We also found that the enzyme responsible for some of these histone modifications, histone deacetylase 4 (HDAC4), was significantly decreased relative to controls in differentiating but not in proliferating cells exposed to CP.…”
Section: Discussionmentioning
confidence: 99%